The profits of mainstream sustainable investing – ESG equity index performance in Europe, the US and the Pacific - Lucenius, Janica (My University, 2016)
Environmental, social and governance (ESG) investing is a continuum of a large trend of social and environmental awareness, which has gained footage among consumers, organizations and finally investors. ESG investing is an investment philosophy, which according to its name seeks to promote ethical business by identifying companies that perform above average on ethical criteria based on three dimensions; environmental, social and governmental. These investments have experienced a massive surge in volume during the recent years and divided scholars on both empirical and theoretical levels on the question of how does the inclusion of non-financial criteria affect financial performance. Since the maturation of responsible investments, ESG is among the most recent and the most popular trends, and potentially advantageous due to being less restrictive than predecessing responsible investing strategies. The premise of this thesis is to contribute to the existing literature by comparatively analysing the performance of ESG stock indices in Europe and the Pacific from 2008 to 2015, and in the US from 2002 to 2015, from two different ESG rating providers. Performance is evaluated through relative performance measures and the Fama and French three-factor and Carhart four-factor models in contrast to benchmark indices with similar stock characteristics from corresponding markets. The regression results show that several of the indices yield negative alphas, and in most cases the ESG indices performed less poorly than conventional indices. Nevertheless, most of the regression results are statistically insignificant, so it is concluded that ESG stocks perform similarly to conventional ones. When comparing the rating providers, there are signs of performance differences in Europe and the US. Winsorsizing suggests that results are partially driven by outliers, as winsorsizing produced a few significant, positive alphas. The results may be affected by the turbulent time period post-financial crisis. In light of the existing studies, more research is needed both on the role of ESG rating providers and the impact of cultural differences.
Keywords: ESG; environmental social governance; sustainable investing; fi=Laskentatoimi ja rahoitus|en=Accounting and Finance|; fi=Master's Degree Programme in Finance|